Rorty’s redescription and the pedagogical context: Enunciation possibilities - Trevisan, Marlon Dantas; Carneiro, Marcelo Carbone [UNESP] (FapUNIFESP (SciELO), 2020)
The text analyzes relations of Rorty’s redescription – neo-pragmatic, analytical philosophical perspective – and approaches on education, with specific objectives: to reflect on epistemology, particularly the abandonment of the notion of knowledge as representation; to meditate on redescription as a metapractice inherent to the contexts of basic and college education, inspiring more libertarian, ethical, creative and political pedagogical routines; to present the redescription named Negociações Cronocapilares, of 2019, produced in the Mid-West, an artistic installation that should circulate among state schools. The redescription, methodology of the essay, proposes a teaching challenge, by questioning, from the foundations of knowing, even educational practices.
A redescrição de rorty e o contexto pedagógico: Possibilidades enunciativas
Keywords: Artistic Intervention; Didactics; Epistemology; Redescription